Synthesis of Nonlinear Automatic Systems - Shakhzod Khojiakbarov (Zien Journals, 2022)
Modern technical systems, as a rule, operate in essentially nonlinear modes, are multicomponent and are described by a large number of state variables. When synthesizing regulators for such systems, one has to face a lack of available control strategies and analysis methods. Traditional (developed for linear systems) methods of design and analysis, when faced with non-linearities, in most cases turn out to be untenable. The theory of designing nonlinear regulators is still under development. Individual methods are very "fragmented", they focus on their own rather narrow class of systems and have individual limitations that do not allow them to be considered from a single point of view.
Keywords: allow; systems; strategies; synthesizing